Os efeitos das desigualdades regionais sobre a desigualdade interpessoal de renda no Brasil, nos estados unidos e no México - Pedro Herculano Guimar\~aes Ferreira de Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper examines the effects of regional inequalities on the interpersonal distribution of household per capita income in Brazil, the United States and Mexico. Five hypotheses are tested through nested decompositions of the GE(0) inequality index applied to Census microdata for all three countries. The results suggest that income inequality is mostly local in Brazil as well as in the United States and Mexico, that is, it occurs among neighbors and thus remains unaccounted for even in municipality-level spatial decompositions. Income inequality in Brazil would still be higher than that of the United States even if it were possible to equalize the average incomes of all Brazilian municipalities. However, this does not mean that regional inequalities are of no consequence to income inequality, as they are also much more pronounced in Brazil and Mexico. The main difference between these two countries and the United States lies in the existence of macro regions with lower average incomes and higher internal inequality than the rest of each country. Both effects are of similar magnitude, so that, in Brazil, lowering local inequality in the North/Northeast is as important as raising the average income of that region in order to reduce interpersonal income inequality.
Keywords: R11; D63; 330; regional inequality; income inequality